Autonomia privada coletiva como instrumento de violação dos direitos fundamentais dos trabalhadores - Colombari, Graziela (2015)
In the practice of law before the Labor Courts, it was observed that at various moments the private collective autonomy granted the union institutions sometimes had their feature corrupted. Once, at some point, it was verified as a way of violating fundamental rights of workers. It questioned up the reasons that were leading those documents that were created to protect the workers to take candid positions of precariousness and suppression of labor rights. In response to questions, focuses on globalization, on the changes in the world of work, on emptying the unions and even on the ethics of those institutions arouse. The interest then turned to fundamental rights in its dual implications, because on the one hand there are rights, benefits to be implemented by society and the State and on the other side they generate duties which are also extended to all involved. In the path, one comes to the Judiciary acting, specifically concerning about the TST, when it faces collective instruments violators of the fundamental rights to evaluate which measures will be implemented and how will the trials work. Anyway, it is a long way to be coursed because there is no prompt answers and each case should be assessed with their respective peculiarities. Evidently, the theme chosen by the Superior Labor Court as representative of the proposed problem (Topic 762) has not been examined by the Supreme Court, returning the issue for analysis of the TST, which, until the conclusion of the present study, was not performed.